Analysis of the right to information in consumer contracts ten years after its regulation in the Civil and Commercial Code (Nueva Epoca, 2025)
This article aims to reflect on the right to information incorporated in the Civil and Commercial Code and its counterpart, the duty to provide information of providers of goods and services in consumer contracts, and its tension with new technologies.
Keywords: Contract; consumption; information; technologies; consent